Pedagogical Content Knowledge (PCK) Based On Local Wisdom To Develop Students’ Nationality Characteristics - Imanuel Sairo Awang; Gabriel Serani; Zuhdan Kun Prasetyo; Muhammad Nur Wangid (Universitas Negeri Makassar, 2021)
The learning process in class must be managed so that students can grow the character in students. The character of students can grow and develop through learning based on local wisdom that has life values. These values are inherent with the values of character in the life of the nation and state. But to design a learning that can develop character requires an integrated study between pedagogy and learning content. The results of this study are outlined in the Pedagogical Content Knowledge (PCK). This study aims to produce PCK based on local wisdom that can develop the national character of elementary school students. To get a decent PCK, the research was carried out using the Research and Development (R&D) approach. The results revealed that, PCK based on local wisdom of the Dayak Desa tribe, was able to improve the behaviour of national character into unity, mutual cooperation, and honesty, each by 0.77; 0.77; and 0.86. Thus, it can be concluded that PCK based on local wisdom can develop the national character of elementary school students.